MODERNISATION OF HIGHER EDUCATION IN UZBEKISTAN: TRANSFORMING QUALITY ASSURANCE SYSTEM AND APPROACHES - Krouglov, Alex (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The paper explores the current transformations in the Quality Assurance (QA) system in the Higher Education (HE) of the Republic of Uzbekistan and examines the impact of the World Bank Modernising Higher Education project which aims, among other issues, to develop and implement a new system of external QA and strengthen the system of internal QA. The research analyses annual and quarterly reports prepared by the Project Team of the Ministry of Higher and Secondary Specialised Education of Uzbekistan, World Bank, Expert Advisory Panel as well as national and international consultants. In addition to this, a series of interviews were conducted with key stakeholders in Uzbekistan. The data received from the analysis of project reports and other documents were triangulated with the data obtained during semi-structured interviews. The research addresses the issues of the process of reforms in QA system at national and university levels and the gradual transformation of QA culture. It covers challenges in the introduction of new QA arrangements and assesses the role of various actors in the process of transformations.